(untitled) (Islamic Sciences Journal, 2023)
This research aims to deep in the deep connotations of grammatical structures came in the words of God: ((and shake you with the trunk of the palm falling on you wet)) of Surat Maryam verse / 25. This is because the grammatical structures are the key to the profound significance of each Arabic text, and by using the rest of the Arabic sciences to discover the splendor of any text Koranic prose or poetic. This research has been organized in five points, the first: to denote the command, the second: to denote the attribute, the third: to denote the preposition (to), and the fourth: to denote the preposition (B), and fifth: to denote the method of submission and delay.